Clóvis Moura e a escrita da história do Brasil (1925-1972): escravidão, questão racial e lutas de classes - Figueiredo, Henrique Roberto (2024)
The present research aims to study the writing of the history of Brazil made by the Piauí native, communist activist and black intellectual, Clóvis Steiger de Assis Moura (1925-2002). It seeks, with special attention, to understand the uses and theoretical developments of the categories “slavery”, “racial issue” and “class struggles” in the set of his historiographical production, interpretation and characterization of the economic-social formation of Brazil, between the years of 1925 and 1972. To this end, he investigates the political and theoretical relationships established with the “historiography of Brazilian slavery”, “Brazilian social thought” and “Marxisms and Marxists in Brazil”, especially with the main Marxist theoretical reference of his generation , historian Caio Prado Júnior (1907-1990). Starting from the hypothesis that Clóvis Moura, when writing and interpreting the history of Brazil until 1972, solved basic problems for his later work, it is understood that these years built the foundation for a work that considers Clóvis Moura as an interpreter of Brazil , producer of a “history of work in Brazil”. The beginning of the investigation from his first years of life does not, however, mean the option of writing an intellectual biography or just an external analysis of the work. It was decided to also investigate elements of his trajectory, intellectual itinerary, process of political consciousness, sociability networks and research choices in order to compose the internal analysis within the milestones of intellectual history, mainly the first two editions of “Senzala Rebellions: quilombos, insurrections, guerrillas” (1959). The investigation is limited to 1972, a landmark change in the object of his investigation from the problems of slavery in colonial Brazil, to the problems of the black population in contemporary Brazil between 1973 and 1977. But, mainly, because in the following year, 1978, his Production would have been influenced by the publication of Colonial Slavery, by Jacob Gorender (1923-2013) and his political activism began to be directed towards the construction of the MNU